The Impotence of Literature in Historical Research: A Critical Study of the Historical Documents of Sultanate Period in Indian Sub-continent - Dr. Sohail Akhtar; Raheela Bibi; Farwa Aiysha; Dr. Nazia Rahat; Rashid-ul-Haq; Dr. Waseem Abbas Gul; Iqra Nazeer (Al-Qanṭara, 2023)
In the analytical study of the past historical contribution of the authors is considered the well enough important evidence as the most integral part of the research, and this article is the critical study of the historical document in the context of the Sultanate of Delhi from the Ghaznavi period to the end of its downfall 1526. The study presents some important and valuable facts as primary documents of the era. This research article explains and highlights the important historical documents relevant to the Sultanate of Delhi.